Diverse mechanisms of resistance to Pseudomonas syringae in a thousand natural accessions of Arabidopsis thaliana - Velásquez, André C (The New phytologist, 2017)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.